2013
DOI: 10.1186/1743-422x-10-152
|View full text |Cite
|
Sign up to set email alerts
|

Co-treatment with arsenic trioxide and ganciclovir reduces tumor volume in a murine xenograft model of nasopharyngeal carcinoma

Abstract: We have previously shown that disruption of promyelocytic leukemia nuclear bodies (PML NBs) is sufficient to activate the EBV lytic cycle thus making infected cells susceptible to ganciclovir (GCV) mediated killing in vitro. Here we show that co-administration of GCV and arsenic trioxide (ATO), a PML NB disruptor, reduces tumor volume in a xenograft model of nasopharyngeal carcinoma utilizing CNE1 cells. When administered at pharmacologic levels, both GCV and ATO reduced tumor growth while co-treatment with GC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Animal model of the human tumor is an indispensable means to study human tumor. The establishment of the animal model of NPC transplantation tumor provides an ideal experimental material and method for the study of NPC [37]. To further investigate the in vivo effect of circRNA CDR1as on NPC, we established an animal model of NPC xenograft tumor and treated mice with si-CDR1as and miR-7-5p mimic.…”
Section: Discussionmentioning
confidence: 99%
“…Animal model of the human tumor is an indispensable means to study human tumor. The establishment of the animal model of NPC transplantation tumor provides an ideal experimental material and method for the study of NPC [37]. To further investigate the in vivo effect of circRNA CDR1as on NPC, we established an animal model of NPC xenograft tumor and treated mice with si-CDR1as and miR-7-5p mimic.…”
Section: Discussionmentioning
confidence: 99%
“…The switch from latent to lytic stage is driven by EBV immediate-early genes, such as BZLF1 (Zta) in vivo or by various commercial reagents in vitro, for example phorbol 12-myristate 13-acetate [ 1 , 2 ], anti-IgG and anti-IgM [ 3 6 ], Ca 2+ ionophore [ 7 ], bone morphogenetic proteins (BMPs) [ 8 ], and transforming growth factor beta 1 (TGF-β1) [ 9 11 ]. Recently, we discovered that arsenic trioxide (ATO) activates the EBV lytic cycle in nasopharyngeal carcinoma cells [ 12 ]. In general, the EBV latent cycle is associated with tumorigenesis because latent genes such as LMP1 are oncogenic, whereas the EBV lytic cycle is often considered detrimental to cell survival.…”
Section: Introductionmentioning
confidence: 99%
“…We previously demonstrated that ATO activates the EBV lytic cycle in EBV-positive epithelial cells and inhibits tumor growth in a xenograft model [ 12 ]. In contrast, in this manuscript we did not find that arsenic induced EBV reactivation in Burkitt’s lymphoma cells.…”
Section: Introductionmentioning
confidence: 99%
“…One proposed method for treating EBV-associated malignancies is the induction of EBV lytic reactivation in latently infected tumor cells (80)(81)(82)(83)(84), which would result in cell susceptibility to cytotoxic antiviral drugs (85). To investigate whether inhibition of LMP1-induced sumoylation results in increased cellular death in response to antiviral therapy, irradiated and mock-irradiated EBV WT-transformed LCLs, EBV dCTAR3-transformed LCLs, and EBV WT-transformed LCLs treated with SUMO inhibitors were treated with ganciclovir (GCV) or a vehicle control (water), and cell death was assayed by trypan blue exclusion (Fig.…”
Section: Lmp1 Ctar3 Is Not Essential For Viral Replicationmentioning
confidence: 99%